Answer: see proof below
Explanation:
Use the following Pythagorean Identities:
sec²A = tan²A + 1
csc²A = 1 + cot²A
Use group factoring: a(x + y) + b(x + y) = (a + b)(x + y)
Proof LHS → RHS
Given: 2sec²Ф - sec⁴Ф - 2csc²Ф + csc⁴Ф
Pythagorean: 2(tan²Ф + 1) - (tan²Ф + 1)² + -2(1 + cot²Ф) + (1 + cot²Ф)²
Group Factoring: (tan²Ф + 1)(2 - tan²Ф - 1) + (1 + cot²Ф)(-2 + 1 + cot²Ф)
Simplified: (tan²Ф + 1)(1 - tan²Ф) + (1 + cot²Ф)(cot²Ф - 1)
Multiplied: tan²Ф - tan⁴Ф + 1 - tan²Ф + cot²Ф - 1 + cot⁴Ф - cot²Ф
Simplified: 1 - tan⁴Ф + cot⁴Ф - 1
= - tan⁴Ф + cot⁴Ф
= cot⁴Ф - tan⁴Ф
cot⁴Ф - tan⁴Ф = cot⁴Ф - tan⁴Ф
![\checkmark](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2v4z11vsn0bdvhj920fbk7f97ux40axw6u.png)